Studies on Ethnomedicine in Buldhana District Of Maharashtra (India) - Patil D. A.*, Dushing Y. A. and (Journal of Phytology, 2011)
The present paper deals with plants used in Buldhana district (Maharashtra), India.Â The ethnobotanical survey was carried out during 2007-2009 in different seasons. The tribal and rural folks although illiterate and socio-economically backward, they have rich traditions of ethonomedicines passed from one generation to another. Methodologies used to investigate ethnomedicinal clams include weekly regular visits, collections of information from tribal and rural medicinmen, other elderly persons and patients in the area under study. This paper includes ethnomedicinal revelations on 48 plant species belonging to 47 genera and 35 angiospermic families. Of these, ethnomedicinal claims from 39 species are unreported earlier from India. The local people have unique knowledge to cure as many as 31 different human diseases or disorders. The ethnomedicinal recipes are in the form of extract, juice, decoction, oil, powder and paste. Various domestic substances e.g. milk; ghee, jaggery, coconut oil, cloves, turmeric powder, etc. are also employed for preparing medicinal recipes. Nearly all aerial and underground parts are used in them. Medicinal plant knowledge of these local people will help reveal new methodology/ drugs for welfare of mankind. Further scientific investigations are desirable to verify their efficacy and toxicity. Key words: Ethnomedicine, Traditional knowledge, Buldhana districts, India <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Dushing Y. A. and Patil D. A. Studies on Ethnomedicine in Buldhana District Of Maharashtra (India). J Phytol 2/12 (2010) 35-41.